Program Bimbingan Karier Dalam Meningkatkan Kesiapan Kerja Warga Binaan Menjelang Pembebasan Di Rutan Kelas II B Situbondo - Setiawan, Andre; Fawaid, Ahmad Rizqian; Zalwadi, Feri (CV. SINAR HOWUHOWU, 2025)
This study aims to describe the implementation of the career guidance program and analyze its contribution in improving the readiness of inmates before release in Situbondo Class IIB Detention Center. The research approach used is qualitative with a case study method, with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that the career guidance program that includes skills training, career guidance, and provision of the world of work has a positive influence on increasing the knowledge, motivation, and self-confidence of inmates in preparing themselves to enter the world of work after release. Furthermore, instructor support, the availability of training facilities, and collaboration with external parties are important contributing factors in determining the program's success. This study concludes that career guidance plays a strategic role in improving inmates' readiness, and therefore recommends its expansion and quality improvement to support a more effective social reintegration process.